Nafkah Madyiyah for Children in Supreme Court Plenary Session 2019 as a Reform of Islamic Family Law in Indonesia - Anwar Muhammad Radiamoda; Nor Arif Saefudin; Alfi Syahrin (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This study is intended to examine the formulation of the results of the 2019 Plenary Meeting of The Supreme Court of the Republic of Indonesia relating to the nafkah madhiyah for children. This formulation is important, because previously the Supreme Court through its decision number 608K/AG/2003 stated that a child's nafkah madhiyah cannot be prosecuted after a husband and wife divorce, so this Supreme Court decision is often used as jurisprudence by judges to reject lawsuits about nafkah madhiyah for child. However, by issuing the formulation of the results of the plenary meeting, The Supreme Court opened up the opportunity for a lawsuit regarding the nafkah madhiyah for child. This study is a normative legal study by relying on library data, then providing an ushul fiqh approach, especially mashlahah analysis. This study shows that the plenary meeting of the Supreme Court chambers in 2019 not only provided a different formulation from the previous decision, but also showed a different paradigm in viewing the livelihood of children. If the previous The Supreme Court decision views the nafkah madhiyah for child as li al-intifa', that is, living as the fulfillment of benefits only and cannot be prosecuted if the benefits have been fulfilled even though the material is not provided, then the formulation of the Plenary Meeting of the Supreme Court positions the nafkah madhiyah for child as li al-tamlik, namely maintenance as a child's property that can be sued if the material is not fulfilled. This formula contains useful values, in accordance with Islamic law, and is relevant to laws and regulations related to children's rights, human rights, and the elimination of domestic violence.